2016
DOI: 10.1039/c5ra25539b
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the structure and the mechanical properties of epoxy–silica sol–gel hybrid materials

Abstract: A new epoxy–silica porous material prepared via one-pot sol–gel process. Mechanical properties can be continuously tuned by modifying reactant proportions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Considering that According to the experimental data, the researchers found that the flexibility and robustness of the pore structure can be enhanced via the combination with polymers. Domènech et al [132] synthesized a porous organic-inorganic hybrid material composed of silica and epoxy resin via a one-pot sol-gel process and subsequent supercritical drying. These results prove that controlling the bridged alkoxide proportions to enhance the mechanical properties of the silica aerogel is feasible and that the strain at 18 N can achieve 80%.…”
Section: Epoxidementioning
confidence: 99%
“…Considering that According to the experimental data, the researchers found that the flexibility and robustness of the pore structure can be enhanced via the combination with polymers. Domènech et al [132] synthesized a porous organic-inorganic hybrid material composed of silica and epoxy resin via a one-pot sol-gel process and subsequent supercritical drying. These results prove that controlling the bridged alkoxide proportions to enhance the mechanical properties of the silica aerogel is feasible and that the strain at 18 N can achieve 80%.…”
Section: Epoxidementioning
confidence: 99%
“…Silicone has the advantages of heat resistance, weather resistance, hydrophobic, low surface energy, good flexibility, and so on. The modification of epoxy resin with silicone can not only reduce the internal stress, but also improve the toughness and heat resistance 12–18 . The modification methods include physical modification and chemical modification.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of epoxy resin with silicone can not only reduce the internal stress, but also improve the toughness and heat resistance. [12][13][14][15][16][17][18] The modification methods include physical modification and chemical modification. The physical blending modification is simple and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Considering feasible and worthwhile ways to enhance the structural strength of silica aerogel, several researchers have recently tried to focus on synthesizing hybrid organic–inorganic silica aerogels in which different organic or synthetic polymers are crosslinked with the silica aerogel using various crosslinkers. For instance, polyurea, epoxides, polyacrylates, polyimides, and polystyrene polymers have been crosslinked with pristine silica aerogel by using diisocyanates, (3-aminopropyl)triethoxysilane, acrylates, anhydrides, and vinyl trimethoxysilane, among others, as the crosslinker, respectively [ 13 , 22 , 23 , 24 , 25 , 26 , 27 ]. Moreover, radical polymerization of alkene and vinyl-functionalized monomers represents another effective reinforcement method based on vinyl trimethoxysilane, vinylmethyldimethoxysiloxane, or vinylmethyldiethoxysiloxane to enhance the mechanical properties and stability of silica aerogel [ 21 , 28 ].…”
Section: Introductionmentioning
confidence: 99%